2019
DOI: 10.3390/su11247149
|View full text |Cite
|
Sign up to set email alerts
|

Assessing SMEs’ Sustainable Growth through Entrepreneurs’ Ability and Entrepreneurial Orientation: An Insight into SMEs in Côte d’Ivoire

Abstract: In most countries, small and medium-sized enterprises (SMEs) play a key role in driving sustainable economic growth and job creation; hence, the need to investigate factors (e.g., entrepreneurial factors) that influence SMEs' sustainable growth (SMESG). This study provides an insight into entrepreneurs' abilities (EAs) that affect SMESG in Côte d'Ivoire (a middle-income economy located in the West African region) and an assessment of the extent to which entrepreneurial orientation (EO) influences the EA-SMESG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 65 publications
1
35
0
1
Order By: Relevance
“…Organisational Culture and Sustainable Growth of SMEs Diabate et al (2019b) confirmed that there is a singnificant relationship between small and mediumsized enterprises sustainable growth (SMESG) and each entrepreneurial ability (EA) dimension such as creativity, risk control, relationship and/or opportunity detection ability) and learning ability accepted. In a similar vein, (Al Badi, 2019) has found that organizational culture was related to the whole society's culture, which has changed over recent years due to changes in lifestyle and consumer behaviour in (Srisathan et al, 2020) reported that there was a significant effect of organizational culture on organizational sustainability in that cultural characteristics maintain the core business competencies in terms of marketing, operations, customer orientation, capital management, and monitoring & evaluation for sustainability (Mohammed et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Organisational Culture and Sustainable Growth of SMEs Diabate et al (2019b) confirmed that there is a singnificant relationship between small and mediumsized enterprises sustainable growth (SMESG) and each entrepreneurial ability (EA) dimension such as creativity, risk control, relationship and/or opportunity detection ability) and learning ability accepted. In a similar vein, (Al Badi, 2019) has found that organizational culture was related to the whole society's culture, which has changed over recent years due to changes in lifestyle and consumer behaviour in (Srisathan et al, 2020) reported that there was a significant effect of organizational culture on organizational sustainability in that cultural characteristics maintain the core business competencies in terms of marketing, operations, customer orientation, capital management, and monitoring & evaluation for sustainability (Mohammed et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…For SMEs' growth, respondents were asked to indicate how their businesses have grown given the current tax administration and incentives on a 5-point Likert scale rated from 1-No improvement-5-Very great improvement (12 items). The items were obtained from empirically validated sources (Nastasiea & Mironeasa, 2019;Wiklund, Patzelt & Shepherd, 2009;Dobbs & Hamilton, 2007;Diabate, Sibiri, Wang & Yu, 2019;Dalrymple, 2004). On measuring tax administration, the respondents were asked to indicate their level of satisfaction with the tax administration items (8 items) on a 5-point Likert scale rated as follows: 1=Not at all satisfied to 5-Extremely satisfied.…”
Section: Methodsmentioning
confidence: 99%
“…The use of growth as a measure of firm performance is generally based on the belief that growth is a precursor to the attainment of sustainable competitive advantage and profitability (Markman & Gartner, 2002). Growth epitomizes the process of in-depth development and positive improvement that is generally measured through quality, and/or profit improvements (Diabate, Sibiri, Wang & Yu, 2019). Finance, number of workers, quality of labour skills, business expansion/branches, product lines, business innovation, search for improvement, market development, sales revenue, productivity, integration of IT in business processes are key measures of SMEs' growth (Xu et al, 2019).…”
Section: Firm Size As a Moderatormentioning
confidence: 99%
“…They create job opportunities and are an important driver of growth in the gross domestic product (GDP). As for the moderating effect of entrepreneurial orientation (EO), innovativeness in entrepreneurship positively and significantly regulates the entrepreneur's ability (EA)-SMEs' sustainable growth (SMESG) relationship; proactiveness positively regulates the relationship between almost all EA dimensions and SMESG, and risk tendency regulates the EA-SMESG relationship in terms of creativity and ability to control risk [34,35].…”
Section: Conceptual Frameworkmentioning
confidence: 99%